2015
DOI: 10.1590/s1806-92902015000800002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photoperiod on sexual activity of boar

Abstract: -The main objective of this study was to assess the effect of photoperiod on sexual activity of three breeds of boars: Swedish Landrace (n=34), Large White (n=38), and Duroc (n=32). Boar sexual activity was analysed based on the libido index and intensity of ejaculation. The libido index was calculated as the ratio between the duration of ejaculation and time of preparation until ejaculation. The intensity of ejaculation was the volume of ejaculate (mL) secreted in the unit of time (min). The effect of photope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The lack of association between BT compound concentrations and DTS might be explained also by the fact that, in this study, measurement of DTS included also the ejaculation time, which is frequently used as an indicator of libido [ 40 ]. Reports on the duration of ejaculation in the boar vary from 3 to 20 min [ 41 ], so a long ejaculation time, which may be an indicator of good libido [ 42 , 43 ], can lead to increased overall DTS when compared with short ejaculation or no ejaculation.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of association between BT compound concentrations and DTS might be explained also by the fact that, in this study, measurement of DTS included also the ejaculation time, which is frequently used as an indicator of libido [ 40 ]. Reports on the duration of ejaculation in the boar vary from 3 to 20 min [ 41 ], so a long ejaculation time, which may be an indicator of good libido [ 42 , 43 ], can lead to increased overall DTS when compared with short ejaculation or no ejaculation.…”
Section: Resultsmentioning
confidence: 99%
“…According to Wysokińska and Kondracki [ 17 ], boars of the Duroc breed need less time to begin ejaculation than Pietrain boars and two-breed crosses. There are studies indicating that male libido may be affected by the season of the year [ 21 , 22 , 23 ], as well as by muscularity and growth rate [ 24 ]. However, the main source of variation seems to be the boar’s individual semen being collected when mounting a phantom and its ability to respond to the phantom.…”
Section: Discussionmentioning
confidence: 99%
“…Data presented by Szostak and Sarzyńska [ 7 ] indicate that the time needed to begin ejaculation has a wide range from 1.99 to 14.65 min, depending on the breed of boar. Savić and Petrović [ 23 ] reported a relatively shorter time needed for boars to begin ejaculation, ranging from 2 to 7 min (120–420 s) depending on the breed and day length. The results of the present study are similar to those reported by Kondracki et al [ 8 ], ranging from 245 to 289 s, depending on the length of the ejaculation period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotype relationship of the traits of sexual activity indicates the possibility of simultaneous improvement of these traits (Savić and Petrović, 2015b). A weak relationship (r<0.2000) exists between libido and intensity of ejaculation, but values of coefficients are positive what makes possible simultaneous improvement of both traits.…”
Section: Libidomentioning
confidence: 99%